(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
High-temperature tempering of cold-rolled martensite in st37 low carbon steel is studied. Different reductions in thickness are considered and compared with the behavior of as-quenched martensite during tempering. Tempering of the as-quenched martensite is accompanied by the formation of carbide particles, incomplete disappearance of the lath martensite morphology, and continuous decrease in hardness until reaching low values. However, during tempering of the cold rolled martensite, the precipitation of carbides in the lamellar structure, development of distinct equiaxed ultrafine grains through a continuous recrystallization mechanism, and a sudden hardness drop is characterized. The importance of cold rolling reduction and its amount are also discussed.